2008
DOI: 10.1073/pnas.0707157105
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective priorities for global mammal conservation

Abstract: Global biodiversity priority setting underpins the strategic allocation of conservation funds. In identifying the first comprehensive set of global priority areas for mammals, Ceballos et al. [Ceballos G, Ehrlich PR, Soberó n J, Salazar I, Fay JP (2005) Science 309:603-607] found much potential for conflict between conservation and agricultural human activity. This is not surprising because, like other global priority-setting approaches, they set priorities without socioeconomic objectives. Here we present a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 42 publications
4
116
0
1
Order By: Relevance
“…Considering that ∼14% of the Earth's land area is already protected (46), the 3.6% of unprotected land that we identified here as key areas for mammal conservation could inform efforts to expand the system of currently protected areas to achieve the Aichi Target 11. However, setting aside areas for conservation incurs socioeconomic and political costs, such as land acquisition value, social conflicts, and political willingness (7,35). Therefore, the priority areas provide a key biodiversity layer for future conservation planning that should be considered along with the priority areas of other taxonomic groups and economic, social, and political considerations (7,12,35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that ∼14% of the Earth's land area is already protected (46), the 3.6% of unprotected land that we identified here as key areas for mammal conservation could inform efforts to expand the system of currently protected areas to achieve the Aichi Target 11. However, setting aside areas for conservation incurs socioeconomic and political costs, such as land acquisition value, social conflicts, and political willingness (7,35). Therefore, the priority areas provide a key biodiversity layer for future conservation planning that should be considered along with the priority areas of other taxonomic groups and economic, social, and political considerations (7,12,35).…”
Section: Resultsmentioning
confidence: 99%
“…However, setting aside areas for conservation incurs socioeconomic and political costs, such as land acquisition value, social conflicts, and political willingness (7,35). Therefore, the priority areas provide a key biodiversity layer for future conservation planning that should be considered along with the priority areas of other taxonomic groups and economic, social, and political considerations (7,12,35). They also highlight biologically important, unprotected regions of the globe that can be used to guide future conservation planning at both regional and global scales.…”
Section: Resultsmentioning
confidence: 99%
“…While opportunity costs of conservation derived from agricultural rental are often used to minimize socio-economic costs of conservation [6,16,17], we opted against their use as they are poorly correlated with the prices for which lands are acquired for conservation [18]. Further, even accurate estimates of monetary opportunity costs are not always indicative of the socio-economic costs to local populations, for instance in areas where the main activity is subsistence farming [19].…”
Section: Methods (A) Protected Area Expansion By 2020mentioning
confidence: 99%
“…Most species' distributions include several countries (mean of 5.87 countries/species) and the median size of mammal ranges is 198.326 km 2 , almost three times larger than the median of country sizes (70.904 km 2 -United Arab Emirates) [74]. Even species with restricted ranges are often transboundary in distribution, making it clear that most mammals will be conserved only with cooperation between countries [10].…”
Section: From Planning To Conservation (A) Whose Plans? Whose Prioritmentioning
confidence: 99%
“…Indonesia, Mexico, India, Brazil and China have the highest number of threatened species, a reflection of the countries' large size and high species diversity [9]. Carwardine et al [10] analysed the area required to represent a target of 10 per cent of the geographical range of each mammal species and found that the greatest amount of irreplaceable area is in Indonesia, Mexico and Papua New Guinea. The forest biome has the highest number of mammal species and the largest proportion of threatened species, especially in the tropical areas of South America, Central Africa and Southeast Asia [9].…”
Section: Mammal Conservation In Contextmentioning
confidence: 99%